PHARMACIST ASSISTANTS IN SAUDI ARABIA: INVESTIGATING THEIR ROLES, CHALLENGES, PROFESSIONAL DEVELOPMENT, AND IMPACT ON PATIENT CARE AND MEDICATION SAFETY - Fawzi Mohammed Saleh Alamri, ‏Sultanah Ali Alamri, Huwaydaa Aliwi Daghim Alanzi, ‏Nasser Nijr Helal Alotaibi, ‏Mohammad Saleh Alanazi, ‏Ahmed Barrak Aldawsari, ‏Abdulaziz Abdulrahman Alabdulwahed, (Chelonian Research Foundation, 2022)
This research paper explores the roles, challenges, professional development, and impact of pharmacist assistants on patient care and medication safety in Saudi Arabia. Through a mixed-methods approach, the study aims to provide a comprehensive understanding of the current state of pharmacist assistants in the country and identify areas for improvement. A survey was conducted with 150 pharmacist assistants, and semi-structured interviews were conducted with 20 pharmacist assistants and 10 pharmacists. The findings reveal that pharmacist assistants play a crucial role in supporting pharmacists and contributing to patient care. However, they face challenges such as limited career advancement opportunities and inadequate training. The study highlights the need for structured professional development programs and the integration of pharmacist assistants into the healthcare team to enhance patient care and medication safety. This research contributes to the understanding of the importance of pharmacist assistants in the Saudi Arabian healthcare system and provides recommendations for optimizing their roles and improving their professional growth.